2022
DOI: 10.5565/rev/catjl.387
|View full text |Cite
|
Sign up to set email alerts
|

The Syntax of Old Catalan Clitics: “Llibre dels Fets”

Abstract: Although the distribution of pronominal clitics in Old Catalan has been described in general terms (Fischer 2002; Batllori et al. 2005), there are no quantitative studies detailing the frequency of preverbal or postverbal clitics nor their diachronic evolution. The clitics appearing with verbs in the future and conditional tense (FC) are worth a separate mention, since these forms originate from periphrastic structures that involve an infinitive and the auxiliary verb habere, and which could appear as an analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Regarding clitic placement, some studies on present-day Galician (Álvarez Blanco et al 1986) and Old Castilian (Granberg 1988(Granberg , 1999Castillo Lluch 1996;Bouzouita 2008aBouzouita , 2008bBouzouita , 2011Bouzouita , 2012Bouzouita , 2016 have observed that this pragmatic function (emphasis) accounts for the presence of preverbal clitics in the aforementioned syntactic environments. Similar behaviour has also been recently observed in Old Catalan (Bouzouita and Sentí 2022;Sentí and Bouzouita 2022;Torres-Latorre 2023). Even so, a detailed exploration of the consequences of information structure in clitic placement in Old Romance languages is still pending.…”
Section: Clitic Placement In Old Catalansupporting
confidence: 87%
See 4 more Smart Citations
“…Regarding clitic placement, some studies on present-day Galician (Álvarez Blanco et al 1986) and Old Castilian (Granberg 1988(Granberg , 1999Castillo Lluch 1996;Bouzouita 2008aBouzouita , 2008bBouzouita , 2011Bouzouita , 2012Bouzouita , 2016 have observed that this pragmatic function (emphasis) accounts for the presence of preverbal clitics in the aforementioned syntactic environments. Similar behaviour has also been recently observed in Old Catalan (Bouzouita and Sentí 2022;Sentí and Bouzouita 2022;Torres-Latorre 2023). Even so, a detailed exploration of the consequences of information structure in clitic placement in Old Romance languages is still pending.…”
Section: Clitic Placement In Old Catalansupporting
confidence: 87%
“…First, the variation permitted between a more grammaticalized construction, i.e., SFC-p, and a less grammaticalized version of the FC, i.e., the AFC, since these forms appear in the same syntactic contexts. As previous studies have shown, both constructions are frequent in Old Catalan (Bouzouita and Sentí 2022;Sentí and Bouzouita 2022;Torres-Latorre 2023). However, this was not the case in Old Castilian.…”
Section: Objectivessupporting
confidence: 61%
See 3 more Smart Citations